La Maladie de Huntington - Pinette, Jean-Baptiste; Pinette, Johnny (Canada, 2012)
Several members of the Régis-Pinette family are suffering from a degenerative disease of the brain: Huntington's Disease. Jean-Baptiste, one of the only members of the family who is not affected, and his brother Johnny, show the reality of living with such a disease.
Verzio Film Festival Submission
Keywords: Canada